Comparative morphology, biology and phylogeny of terminalâ€instar larvae of the European species of Toryminae (Hym., Chalcidoidea, Torymidae) parasitoids of gall - GÓMEZ, J F (Zoological Journal of of the Linnean Society, 2008)
We present a phylogenetic and taxonomic study of the morphology and biology of the terminal-instar larval stage of 19 species representing all the genera of Torymidae parasitoids of gall wasps in Europe, with the single exception of Megastigmus. The genera studied include Adontomerus Nikol’skaya, Idiomacromerus Crawford, Chalcimerus Steffan & Andriescu, Glyphomerus Förster, Pseudotorymus Masi and Torymus Dalman. We primarily used chaetotaxy and some head structures. The terminal-instar larvae of all studied species are thoroughly described for the ﬁrst time and illustrated with SEM images. We provide diagnostic characters for the family and the genera studied, and keys to genera and species for the identiﬁcation of torymid larvae associated with cynipid galls. The majority of the torymid larvae studied are solitary monophagous parasitoids. Finally, to assess the potential use of larval characters in systematic studies of the family, a phylogenetic analysis of the studied taxa based on 42 larval morphological characters is proposed and compared with the current taxonomy of Torymidae. Our results suggest that body chaetotaxy, and characters of the head and mouthparts could be used for genera and species discrimination.
Keywords: cynipid galls; food webs; identiﬁcation key; immature stages

Comparative morphology, biology and phylogeny of terminalâ€instar larvae of the European species of Toryminae (Hym., Chalcidoidea, Torymidae) parasitoids of gall - GÓMEZ, J. F. (Zoological Journal of of the Linnean Society, 2008)
We present a phylogenetic and taxonomic study of the morphology and biology of the terminal-instar larval stage of 19 species representing all the genera of Torymidae parasitoids of gall wasps in Europe, with the single exception of Megastigmus. The genera studied include Adontomerus Nikol’skaya, Idiomacromerus Crawford, Chalcimerus Steffan & Andriescu, Glyphomerus Förster, Pseudotorymus Masi and Torymus Dalman. We primarily used chaetotaxy and some head structures. The terminal-instar larvae of all studied species are thoroughly described for the ﬁrst time and illustrated with SEM images. We provide diagnostic characters for the family and the genera studied, and keys to genera and species for the identiﬁcation of torymid larvae associated with cynipid galls. The majority of the torymid larvae studied are solitary monophagous parasitoids. Finally, to assess the potential use of larval characters in systematic studies of the family, a phylogenetic analysis of the studied taxa based on 42 larval morphological characters is proposed and compared with the current taxonomy of Torymidae. Our results suggest that body chaetotaxy, and characters of the head and mouthparts could be used for genera and species discrimination.
Keywords: cynipid galls; food webs; identiﬁcation key; immature stages